Parametric Models for Predicting the Performance of Wind Turbines. (2020) - Veena, R.; Manuel, S.M.; Mathew, S.; Petra, I.
Abstract: Performances of eight parametric power curve models for wind turbines, which can be used for the planning and management of wind energy projects, are compared in this study. Initially, the manufacturer's power curves of four wind turbines are compared with their field performances. Then, the parametric models are developed for these turbines which are tested with their site performances. Out of the models, WERA showed the best performance in case of all the turbines. Finally, a method for using WERA in extrapolating the performance of turbines with limited test data is demonstrated with the case of a 1 kW turbine.